Ethnonursing for Utilizing Complementary Therapy at using Tribes in Banyuwangi - Hanny Rasny; Tantut Susanto; Erti Ikhtiarini Dewi (Jurnal Ners, 2014)
Introduction: Using Tribe in Banyuwangi until today still using natural resources as a traditional treatment or care. This study was purposed to gain value and meaning of Using Tribe experience for utilizing complementary therapies in traditional healing practice.Methods: Phenomenology study with qualitative methods based on ethnonursing models was used for this research. There were 13 respondents gathered by purposive sampling from three districts: Glagah, Rogojampi and Banyuwangi Kota. The data were obtained by conducting in-depth interviews on respondents and field observations as well as observations while interview. The analysis carried out by sorting and selecting a word or phrase that has value and meaning to the goal related with sub-themes grouped into themes and categories.Results: The results had showed that Using Tribe’s characteristic were social cohesion, appreciate arts, performing daily activities on the river, consume foods of animal and vegetable, not too close with health service, the myth factor was a strong factor in health and physical maintenance’s behavior, the the use of herbs and shaman to treat health problems.Conclusion: The use of herbs is suitable with modern health science as a complementary therapy, but this point almost faded because it tends to rarely performed. So, the Using Tribe need positive reinforcement from nurses, as an effort to improve their health status.'